Experimental Studies on the Relative Efficacy of Dermatan Sulphate and Heparin as Antithrombotic Agents - Merton, R E; Thomas, D P (Thrombosis and Haemostasis, 1987)
In this study, the anticoagulant and antithrombotic properties of unfractionated heparin (UFH) and dermatan sulphate (DS) were compared. The ability of UFH and DS to impair thrombin generation in vitro and in ex vivo plasma samples was also studied. DS has minimal anticoagulant activity by conventional assays but impairs thrombin generation both in vitro and in ex vivo plasma samples. However, thrombin generation could not be suppressed below about 35% of control values at all doses of DS studied. While this was sufficient to impair experimental venous thrombosis during 10 minutes’ stasis, DS was ineffective in preventing thrombosis following 20 minutes’ stasis in doses up to 1.25 mg/kg. In contrast, 1 μg/ml of UFH completely suppressed thrombin generation in vitro, and 150 μg/kg prevented throm- bogenesis over a period of 20 minutes’ stasis. Neither drug prolonged the bleeding time (BT) at effective antithrombotic doses, but 2.5 mg/kg UFH significantly increased the BT, whereas DS did not. While DS has antithrombotic activity, it is less effective than UFH in inhibiting thrombin generation, and as an antithrombotic agent.
Keywords: Venous thrombosis; Dermatan sulphate; Heparin; Thrombin generation